2020
DOI: 10.1088/1755-1315/612/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of diffusion of leaked soluble hazardous chemicals in the Daya Bay, China

Abstract: Based on observation data and temperature diffusion experiment of soluble hazardous chemicals, propylene oxide was taken as a typical hazardous chemical to simulate diffusion after leakage in conditions of variable locations, source intensities, and tides in the Daya Bay by FVCOM model. The results show no unsafe concentration (0.02 mg/L) area after 24 hours for leakage of 100 tons occurring in channel and anchorage, and over 3 km2 unsafe area for the same amount of leakage occurring in port. There are more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Zhang et al [7] carried out tracer field experiments in DYB, and the observation-based estimations showed that the diffusion coefficient of pollutants was much larger in the meridional direction than in the zonal direction. Through model experiments, Ge et al [8] investigated the potential distributions of oil films in the DYB after different oil spill amounts. But the simulation time only lasted for 24 hours, which was probably not able to reflect the long-term dispersion trend of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [7] carried out tracer field experiments in DYB, and the observation-based estimations showed that the diffusion coefficient of pollutants was much larger in the meridional direction than in the zonal direction. Through model experiments, Ge et al [8] investigated the potential distributions of oil films in the DYB after different oil spill amounts. But the simulation time only lasted for 24 hours, which was probably not able to reflect the long-term dispersion trend of pollutants.…”
Section: Introductionmentioning
confidence: 99%